Estimasi Sumber Daya Bijih Besi Menggunakan Metode Inverse Distance Weighted dan Ordinary Kriging di PT.KUATASSI, Kabupaten Solok, Sumatera Barat - Muhammad Rizky; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2022)
PT. Karya Usaha Aneka Tambang Solok Selatan Indonesia is a company engaged in iron ore mining in Danau Kembar District, Solok Regency, West Sumatra with a mining business permit area of 31 hectares. PT. Karya Usaha Aneka Tambang Solok Selatan Indonesia has carried out further exploration and drilled 11 drill holes. This study has purpose to modeling, analyzing, and validating estimation method used for the assessment of iron ore resources at PT. Karya Usaha Aneka Tambang Solok Selatan Indonesia. The method used in this research is Inverse Distance Weighted (IDW) and Ordinary Kriging (OK) using Surpac 6.5.1 software. The block model made with the size of the model block units is 5x5x1 meter. The accuracy of the two methods in the assessment will be compared using downhole composite validation. In this study, the data used is data from detailed exploration drill activities of 11 drill holes with 254 composite data. From the results of the study, the estimation of the IDW method was obtained from all resources, namely 524,115 tons with a volume of 137,925 m3 and an average Fe content of 37.50%. And for the OK method estimation, the amount of all resources is 288,990 tons with a volume of 76,050 m3 and an average Fe content of 37.50%. Based on the validation using the composite downhole of each method, the IDW method gets results that are closest to the composite value and get a value that is greater than the OK method. So the volume that will be used in various decision making for the purposes of further exploration, mine planning and other technical matters is the volume of the IDW method.